Water security: old concepts, new package, what value? - Lautze, Jonathan F.; Manthrithilake, Herath (2014)
The term water security has infiltrated prominent discourse in the international water and development communities, but achieving it is often viewed as a new water sector target. Despite the elevated status that the concept has increasingly acquired, the understanding of the term is murky and quantifying it is rare. To promote a more tangible understanding of the concept, the authors have developed an index for evaluating water security at the country level. The index comprises indicators in the five components considered to be critical to the concept: (i) basic needs, (ii) agricultural production, (iii) the environment, (iv) risk management, and (v) independence. Achieving water security in these components can be considered necessary, but insufficient criteria, for measuring the achievement of security in related areas, such as health, livelihoods, and industry. After populating the indicators with data from Asia-Pacific countries, the results are interpreted and the viability of the method is discussed. This effort comprises an important first step in quantifying and assessing water security across countries, which should spur a more concrete understanding of the term and discussion of its added value.